Effects of COVID-19 on malaria elimination initiatives in sub-Saharan Africa: a scoping review protocol - Nunu, Wilfred Njabulo; Ndirangu, James; Tsoka-Gwegweni, Joyce (BMJ open, 2023)
IntroductionThe occurrence of the COVID-19 pandemic significantly impacted health systems, resulting in varied outcomes of different variables in terms of health. Due to the nature of the causative organism that is spread mainly in the air, the disease rapidly spread to numerous countries, leading to a series of mitigation measures being proposed and implemented, including but not limited to travel restrictions, decongesting and in some instances closure of workplaces and schools and banning of social gatherings. This could have negatively impacted implementing strategies meant to ensure the effective management of malaria, hoping to eliminate it in different countries in sub-Saharan Africa (SSA). This review seeks to explore the effect of the COVID-19 pandemic on malaria elimination initiatives in SSA.Methods and analysisAn exploratory scoping review will be conducted on literature (searched using keywords and a search strategy) sources published in English on Web of Science, Cochrane Library, PUBMED, Dimensions, ProQuest, Scopus and African Journals Online. These would then be imported to Rayyan Software for screening for possible inclusion. The JBI Guidelines on Reviews, Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews checklist would guide the data collection, extraction and analysis from the accessed literature. Furthermore, charting, trends and developing themes would ensure the findings are presented comprehensively and yet understandable. The data collection and analysis process leading to the final submission of a review paper to a journal will be conducted from September 2023 to February 2024.Ethics and disseminationAn application for ethical approval was lodged with the Health Sciences Research Ethics Committee at the University of the Free State in Bloemfontein, South Africa. This ethics committee granted ethics clearance (ethics number: UFS-HSD2022/1754). Results will be communicated through peer-reviewed publications, presentations, conferences, workshops and other means and forums to reach the critical stakeholders.